2014
DOI: 10.17798/beufen.16242
|View full text |Cite
|
Sign up to set email alerts
|

Ozon ve Gıda Endüstrisinde Kullanım Alanları

Abstract: ÖzetSon yıllarda gıdaların mikrobiyal güvenliğini sağlamak amacıyla radyasyon ve ozon uygulamaları gibi farklı yöntemler uygulanmaktadır. Genellikle düşük konsantrasyonlarda daha kısa temas süresi ile geniş spektrumda mikroorganizma inhibisyonunu sağlayan ozon uygulamaları gıda endüstrisinde başarı ile uygulanabilmektedir. Yüksek reaktivitesi, kendiliğinden parçalanarak ortamda zararlı bileşik bırakmaması ozonun gıdalarda kullanımını güvenilir hale getirmektedir. Ozon son on yıldır pek çok ülkede gıda sanayind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…They stated that the use of UAV and Terrestrial Photogrammetry techniques together is very advantageous in terms of accuracy, speed and cost in 3D modeling studies. Yilmaz et al [3], performed orthophoto map production with UAV data and observed that the results for small-sized areas gave the expected accuracy. Erdogan et al [4] made a 3D model of the Karabıyık Bridge with UAV data.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the use of UAV and Terrestrial Photogrammetry techniques together is very advantageous in terms of accuracy, speed and cost in 3D modeling studies. Yilmaz et al [3], performed orthophoto map production with UAV data and observed that the results for small-sized areas gave the expected accuracy. Erdogan et al [4] made a 3D model of the Karabıyık Bridge with UAV data.…”
Section: Introductionmentioning
confidence: 99%